American Nightmares : Social Problems in an Anxious World. - Best, Joel (University of California Press, 2017)
In an accessible and droll style, well-known sociologist Joel Best shines a light on how we navigate these anxious, insecure social times. While most of us still strive for the American Dream-to graduate from college, own a home, work toward early retirement-recent generations have been told that the next generation will not be able to achieve these goals, that things are getting-or are on the verge of getting-worse. In American Nightmares, Best addresses the apprehension that we face every day as we are bombarded with threats that the social institutions we count on are imperiled. Our schools.